Psychology in the unified social assistance system: inequality and social control (Research, Society and Development, 2022)
The objective of this article is to promote the analysis of the performance of this professional in services linked to public policies in the Unified Social Assistance System. This is a bibliographic research in which printed and electronic literature is used. In the data collection, on the websites of the Center for Technical References in Psychology and Public Policies (CREPOP) and the Federal Council of Psychology (CFP), the main Technical References related to the role of the psychologist in the services of the Unified Social Assistance System (YOUR). Identification of practices that converge with the demands of the SUAS, such as: insertion in the community and group interventions. The work of psychologists, despite the efforts, confirms how much psychology, as a science and profession, has kept a historical distance from social issues, and currently, studies related to psychology are increasingly inserted in social resources, knowing how to deal with this profession, of how to offer assistance to those who depend on the professional, are very important aspects. It was concluded that the individual does not only need social attention, but also qualified hearing, understanding two of his feelings.